Synthesis and Evaluation of Antimicrobial Activity of Nitrones from Derivatives of Aryl-Substituted Dihydroisoquinoline - Mouna Bouzid; Raed Abdennabi; Mohamed Damak; Majed Kammoun (Journal of Chemistry)
This paper describes the synthesis of a series of dihydroisoquinoline nitrones by isomerization of the corresponding oxaziridines. Nitrones 4a–c were obtained in excellent yields and high purity by a simple and effective method from the isomerization of oxaziridines. The synthesized compounds were also evaluated for their antibacterial activity against Gram-positive and Gram-negative bacteria and fungus.